2023
DOI: 10.1002/advs.202300912
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing Algorithmic Design, Photoclick Chemistry and Multi‐Material Volumetric Printing for Accelerating Complex Shape Engineering

Abstract: The field of biomedical design and manufacturing has been rapidly evolving, with implants and grafts featuring complex 3D design constraints and materials distributions. By combining a new coding‐based design and modeling approach with high‐throughput volumetric printing, a new approach is demonstrated to transform the way complex shapes are designed and fabricated for biomedical applications. Here, an algorithmic voxel‐based approach is used that can rapidly generate a large design library of porous structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…[136,137] In particular, Chansoria et al created a heart model wrapped in an auxetic mesh, as seen in Figure 5a. [117] The heart component was volumetrically printed first from norbornene-modified gelatin and thiolated gelatin. Then, the uncrosslinked material was removed from the vial and replaced with a similar resin labeled with rhodamine (rhodlabeled).…”
Section: Vat-switching During Multimaterials Hydrogel Bioprintingmentioning
confidence: 99%
See 2 more Smart Citations
“…[136,137] In particular, Chansoria et al created a heart model wrapped in an auxetic mesh, as seen in Figure 5a. [117] The heart component was volumetrically printed first from norbornene-modified gelatin and thiolated gelatin. Then, the uncrosslinked material was removed from the vial and replaced with a similar resin labeled with rhodamine (rhodlabeled).…”
Section: Vat-switching During Multimaterials Hydrogel Bioprintingmentioning
confidence: 99%
“…Clearly, this work has exciting potential in the field of construction. [117] Copyright 2023, John Wiley and Sons. b) Printed SMP stent with drug-releasing function.…”
Section: Vat-switching During Multimaterials Hydrogel 4d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the potential of multi-material VBP, some using sequential printing of the first material, a washing step to remove the uncrosslinked resin, followed by a second volumetric printing step of the second material, [472,473] or the incorporation of a second printing approach, such as embedded extrusion bioprinting. [474] However, as shown in a recently published study outlining different approaches towards multimaterial VBP, printing two resins in a single step requires some adjustments to their optical properties, [473][473] as well as the establishment of a strong interface that holds both materials together post-printing.…”
Section: Resultsmentioning
confidence: 99%
“…Volumetric printing of cellular structures (volumetric bioprinting), has been demonstrated on various occasions, reporting the possibility to print viable and functional cells and organoids, [127,286] and to sculpt the latter into complex, function-modulating architectures. [286] The potential to create complex multi-material Thermal Shrinking of Biopolymeric Hydrogels for High Resolution Volumetric Printing A constructs, [473] combine the VP approach with other printing strategies, like embedded bioprinting for further multi-material and multi-cellular applications, [474] two-photon ablation to create microchannels withing VP-printed structures, [614] and melt electrowriting to enhance the mechanical stability of printed hydrogel structures, [472] has also been recently demonstrated. In the field of material chemistry however, the use of smart, stimuli responsive bioresins has been limited to date.…”
Section: Introductionmentioning
confidence: 99%